The Role of Clinical Psychology and Peer to Peer Support in the Management of Chronic Medical Conditions – A Practical Example With Adults With Congenital Heart Disease - Callus, Edward; Pravettoni, Gabriella (Frontiers in Psychology, 2018)
Clinical psychology services and peer to peer support can both contribute in increasing the psychological wellbeing of patients with chronic medical conditions. In this perspective paper, indications are given about the provision these services for the specific case of adults with congenital heart disease. These patients are at an increased risk of psychological distress, neurocognitive deficits and social challenges. The psychosocial characteristics and mental health treatment preferences of these patients are briefly described, followed by guidelines and indications for the implementation of clinical psychology services. The mental health treatment preferences of this group when it comes to psychosocial service are illustrated, followed by a description of Tthe most structured peer to peer program available for this population is subsequently illustrated and for this population. Indications are given for the provision of clinical psychology services and peer to peer support, with reference also to specific psychosocial interventions linked to particular types of distress and problems.finally, specific benefits and challenges when it comes to the integration of both services are reported.